Association between Pruritus and Psychosocial Well-being: A Population-based Study among 6,809 Subjects - Suvi-Päivikki Sinikumpu; Jari Jokelainen; Kaisa Tasanen; Markku Timonen; Laura Huilaja (Medical Journals Sweden, 2023)
Pruritus has an extensive impact on functional, social and psychosocial behaviour. The association between pruritus and psychological well-being has mostly been studied among selected patient groups, whereas population-based studies are lacking. The aim of this study was to determine the association between pruritus and insomnia, quality of life, depression and anxiety at the population level in the general population. A cross-sectional population-based study was conducted in 2012 to 2013. Study subjects (n = 6,809) belonging to the Northern Finland Birth Cohort 1966 Study participated in a large follow-up study at the age of 45-47 years. They completed an extensive health questionnaire including questions on pruritus and several previously validated questionnaires regarding symptoms of psychosocial well-being. Pruritus affected 19.9% of the study subjects weekly, being more common in women than in men (p < 0.001). A significant association was found between both localized and generalized pruritus and symptoms of insomnia, depression, anxiety and decreased quality of life. The association was seen even in those with mild psychological symptoms/insomnia, and it affected both sexes. The severity of psychological symptoms increased with increasing frequency of pruritus. In conclusion, pruritus has a multiple effect on psychosocial well-being. Physicians should consider possible psychosocial symptoms in patients with pruritus.